Lignans from Patrinia scabiosaefolia improve insulin resistance by activating PI-3K/AKT pathway and promoting GLUT4 expression - Zhenhua Liu; Mengke Wang; Lijun Meng; Yixiao Chen; Qiuyi Wang; Yan Zhang; Xuefeng Xi; Wenyi Kang (Food Science and Human Wellness)
Patrinia scabiosaefolia, is used as wild vegetable in China for more than 2 000 years, with a variety of pharmacological activities, including anti-inflammatory, anti-tumor and hypoglycemic. Based on our ongoing research on chemical constituents and hypoglycemic activity of P. scabiosaefolia, 4 lignan compounds, (+)-isolariciresinol (1), 7R,7'R,8S,8'S-(+)-neo-olivil-4-O-β-D-glucopyranoside (2), 4-O-methylcedrusin (3) and patrinian A (4), were isolated and identified. The hypoglycemic activity showed that compounds 2 and 3 could extremely significantly improve insulin resistance at 100 (P < 0.001), 50 (P < 0.001) and 25 µmol/L (P < 0.01) in IR 3T3-L1 cells. While compound 4 only promoted glucose uptake by IR 3T3-L1 cells at 100 µmol/L (P < 0.01). Western blotting experiments showed that compounds 2 and 4 up-regulated the protein expressions of p-IRS, PI-3K, p-AKT and glucose transporter 4 (GLUT4), and promoted the transcription of GLUT4 mRNA. Therefore, the mechanisms of compounds 2 and 4 were presumed to improve IR by activating PI-3K/AKT signaling pathway.